Hyaluronidase-4 is produced by mast cells and can cleave serglycin chondroitin sulfate chains into lower molecular weight forms - Farrugia, Brooke L. (J Biol Chem, 2019)
Mast cells represent a heterogeneous cell population that is well-known for the production of heparin and the release of histamine upon activation. Serglycin is a proteoglycan that within mast cell α-granules is predominantly decorated with the glycosaminoglycans heparin or chondroitin sulfate (CS) and has a known role in granule homeostasis. Heparanase is a heparin-degrading enzyme, is present within the α-granules, and contributes to granule homeostasis, but an equivalent CS-degrading enzyme has not been reported previously. In this study, using several approaches, including epitope-specific antibodies, immunohistochemistry, and EM analyses, we demonstrate that human HMC-1 mast cells produce the CS-degrading enzymes hyaluronidase-1 (HYAL1) and HYAL4. We observed that treating the two model CS proteoglycans aggrecan and serglycin with HYAL1 and HYAL4 in vitro cleaves the CS chains into lower molecular weight forms with nonreducing end oligosaccharide structures similar to CS stub neoepitopes generated after digestion with the bacterial lyase chondroitinase ABC. We found that these structures are associated with both the CS linkage region and with structures more distal toward the nonreducing end of the CS chain. Furthermore, we noted that HYAL4 cleaves CS chains into lower molecular weight forms that range in length from tetra- to dodecasaccharides. These results provide first evidence that mast cells produce HYAL4 and that this enzyme may play a specific role in maintaining α-granule homeostasis in these cells by cleaving CS glycosaminoglycan chains attached to serglycin.